Utilization of Latrine and Associated Factors Among Rural Households in Takussa District, Northwest Ethiopia: A Community-Based Cross-Sectional Study. (April 2022) - Omer, Nuruhusan; Bitew, Bikes Destaw; Engdaw, Garedew Tadege; Getachew, Atalay
Background: The use of sanitation facilities is known to interrupt the transmission of fecal-oral related diseases. However, the evidence was limited about the utilization of latrines within the rural community of Takussa district. Therefore, this study was conducted to assess the utilization of latrines and associated factors among households in Takussa district, northwest Ethiopia. Methods: A community-based cross-sectional study design was employed to survey 801 rural households among initially computed 812 participants from February 15 to March 15, 2019. A structured questionnaire with face-to-face interviews was used to collect the data. SPSS version 20 was used to analyze the completed data. A binary logistic regression model was used to process bivariate and multivariable analysis of the data. The adjusted odds ratio was used for the interpretation of the data after controlling for the confounders. Results: The proper latrine utilization rate was 41.9%, with a 95% confidence interval of (38.8, 45.3). Households with school-aged children (AOR: 2.27, 95% CI: (1.44, 3.56), a clean latrine (AOR: 3.34, 95% CI: (1.26, 4.93), the optimal distance from the living room (AOR: 1.56, 95% CI: (1.09, 2.25), and perceived benefit (AOR: 3.64, 95% CI: (1.13, 11.67) were statistically associated factors. Conclusion: The Proper utilization of latrines was low among rural households in the Takussa district. School children, distance, cleanliness, and the benefit of latrines were statistically associated factors. As a result, encouraging health extension workers integrated into district schools to pay special attention to frequent follow-up in order to promote proper latrine utilization at the household level.